2013
DOI: 10.1080/13669877.2012.761272
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between awareness of road safety measure and accident involvement in pre-drivers: the basis of a road safety programme

Abstract: The relationship between awareness of road safety measure and accident involvement in pre-drivers: the basis of a road safety programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Because of demographic differences in the risk behaviors that we assessed, we examined our data for differences between males and females. A substantial literature has reported that males engage in significantly more risk behaviors than females (Arnau-Sabates et al, 2013;Figner & Weber, 2011;Harris, Jenkins, & Glaser, 2006;Pawlowski et al, 2008;Thomson & Carlson, 2015;Wong, Zane, Saw, & Chan, 2013). For example, based on a meta-analysis of 150 studies, Byrnes, Miller, and Schafer (1999) reported that males engage in more risk-taking behaviors than females.…”
mentioning
confidence: 99%
“…Because of demographic differences in the risk behaviors that we assessed, we examined our data for differences between males and females. A substantial literature has reported that males engage in significantly more risk behaviors than females (Arnau-Sabates et al, 2013;Figner & Weber, 2011;Harris, Jenkins, & Glaser, 2006;Pawlowski et al, 2008;Thomson & Carlson, 2015;Wong, Zane, Saw, & Chan, 2013). For example, based on a meta-analysis of 150 studies, Byrnes, Miller, and Schafer (1999) reported that males engage in more risk-taking behaviors than females.…”
mentioning
confidence: 99%
“…Comparable factorization has been encountered in the literature before (e.g. Arnau-Sabatés et al, 2013). Nonetheless, good statistical performance is not a guarantee for logical relevance.…”
Section: Discussionmentioning
confidence: 92%
“…According to Neuburger and Egger (2020), travelers have restrictions and reservations about travel plans to various places during COVID-19, which will influence TBP. Education on understanding the risk factors and care for each other’s emotions while driving on road will alleviate the unpleasant consequences (Arnau-Sabatés et al , 2013) such as road rage or frustrations. Predicting the intention of road users is crucial because the time frame for decision-making while driving is minimal or instantaneous to avoid any difficult situation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%